Optimization problems of power system economic dispatch - Lysenko, L. I.; Makhotilo, Kostiantyn; Cherkashyna, H. I. (FOP Panov A. M., 2021)
The study guide considers mathematical modeling techniques for problems of linear and nonlinear programming in the field of power engineering. Control of power system operation requires specifying economic loading of power plants under various operating conditions as well as optimal electric grid dispatch with minimum active power loss. The first chapter describes linear programming problems of optimal fuel scheduling among power plants and economic electric grid loading. The second chapter deals with economic dispatch problems for thermal and hydropower plants taking into account power loss in the electric grid. The third chapter analyzes minimization of active power loss through optimal reactive power compensation in electric grids of various configurations. The study guide considers numerous examples of various-type optimization problems of power engineering focusing on building mathematical models and searching for optimal solutions with application of Microsoft Excel Solver. The manual contains information that may be helpful for students taking master’s and PhD programs in Electric Power Engineering.
Keywords: study guide; linear programming; power engineering; travelling salesman problem; economic dispatch; hydrothermal power system